A comprehensive performance comparison on the impact of MOF-71, HNT, SiO2, and activated carbon nanomaterials in polyetherimide membranes for treating oil-in-water contaminants. Issue 1 (February 2023) - Sasikumar, B.; Krishnan, S.A. Gokula; Afnas, Muhammed; Arthanareeswaran, G.; Goh, P.S.; Ismail, A.F.
Abstract: The effective treatment of industrial oil/water emulsion before discharging into the receiving bodies is essential to prevent environmental pollution and its negative impacts on human health. The nanomaterial-incorporated nanocomposite membranes are touted as suitable candidates for removing oil contaminants from water. The selection of nanomaterial in nanocomposite membranes is crucial to fit the intended application. In this study, the performance of four different nanomaterials, i.e., metal-organic frameworks-71 (MOF-71), silicon dioxide (SiO2 ), activated carbon (AC), and halloysite nanotubes (HNTs), were used as the nanofiller of membranes. The resultant membranes were characterized by FESEM, AFM, water contact angle, and FTIR analysis. The membrane performance was examined in pure water flux (PWF) and oil/water emulsion rejection studies. The enhancement of PWF in SiO2, HNTs, MOF-71, and AC-based PEI/PVP composite membranes compared to neat PEI/PVP membranes was 33.33%, 59.25%, 70.37%, and 77.77%, respectively. The PEI/PVP/MOF-71 and PEI/PVP/AC membranes exhibited the best performance for PWF and oil/water rejection. Engine oil/water, hexane/water, and toluene/water % rejection of PEI/PVP/AC membrane was found to be 91.98%, 90.55%, and 93.74%, respectively, significantly higher than the neat PEI/PVP membrane. Furthermore, the nanomaterials-incorporated membrane showed better antifouling properties than the neat PEI/PVP membrane due to enhanced hydrophilicity. The MOF-71 and AC nanomaterials-based PEI membranes exhibited good oil/water emulsions separation due to their reliable adsorption capacity and improved fouling resistance than HNTs and SiO2 nanomaterials incorporated membranes, which could have a wide range of membrane-based water treatment applications. Graphical Abstract: ga1 Highlights: Fabricated PEI composite membranes by incorporating MOF-71, HNTs, SiO2 and AC nanomaterials. PEI composite membranes showed enhanced antifouling properties than neat PEI/PVP. MOF-71 and AC based membrane showed higher oil/water flux and rejection than neat PEI/PVP membrane. PEI/PVP/AC membrane exhibited 91.98% rejection for engine oil/water emulsions.